Effectiveness of the SKT Meditation Program on Body Mass Index, Waist Circumference, and Health Behaviors in Overweight Students - Pattakan, Watcharaporn; Teanuan, Yaowalak (The Journal of Chulabhorn Royal Academy, 2025)
The prevalence of adolescent overweight conditions poses a considerable challenge, requiring innovative and effective behavioral interventions. This study utilized a quasi-experimental, one-group time-series design to investigate the efficacy of the SKT Meditation Program on Body Mass Index (BMI), waist circumference (WC), and health behaviors among 27 overweight university students (BMI ≥ 23 kg/m²). Participants engaged in an 8-week SKT program (Techniques 1, 2, and 7) alongside nutrition and 3 A’s 2 S’s health behaviors promotion, with outcomes measured pre- and post-intervention. The results demonstrated a statistically significant elevation in mean scores for nutritional knowledge and 3 A’s 2 S’s health behaviors promotion (p < 0.01), with large effect sizes ( = 2.87 - 4.77). Furthermore, the program led to a statistically significant decrease in BMI, WC, and FBG (p<0.01). Repeated Measures ANOVA established a substantial practical effect size ( : 0.49−0.68) across all physiological variables, with FBG demonstrating a significant and rapid decrease beginning in Week 2 and exhibiting the highest effect size ( = 0.68), indicating a marked efficacy on glucose metabolism. In summary, the SKT Meditation Program exhibits significant potential and minimal expense for enhancing holistic health and mitigating cardiometabolic risk among students, thereby endorsing its implementation as a scalable, integrated health promotion strategy for analogous populations in the future.